Analysis of Mafic rocks Microstructure damage and failure Process under Compression Test Using Quantitative Scanning Electron Microscopy and Digital Images Processing. (15th May 2020) - Tao, Ran; Sharifzadeh, Mostafa; Zhang, Yan; Feng, Xia-Ting
Highlights: Uniaxial compression and triaxial compression tests on the mafic rock specimens were performed. Specimens were scanned by SEM before and after tests and SEM images were obtained. Using digital image processing quantitative analysis of microstructures characteristics effect on macro-scale was presented. Tensile-shear damage ratio at different stages of rock failure process was calculated. The influence of confining stresses on damage pattern were analysed. Abstract: The micro-structures of rock govern meso- and macro-scale rock behaviours and their failure mechanisms. This paper applied the experimental study (uniaxial and triaxial compressive tests) and scanning electron microscope (SEM) method to illustrate the relationship between microscopic damage and mesoscopic fracture. Specifically, this study carried out that there are three main pre-existing micro-structures including heterogeneity (31%), micro-cracks (27%), and crystal lattice boundaries (25%). The pre-existing micro-cracks are investigated and classified as inter-granular cracks (37%), intra-granular cracks (36%), and trans-granular cracks (27%) based on morphological characteristics. According to the deformation types, the micro-cracks after test are divided as tensile crack (53%), shear crack (29%), and mixed shear and tensile crack (18%). Moreover, this paper provides a damage property parameter which is the ratio of tensile damage degree to shear damage degree based on the SEM image processing technique. This parameter could reveal the damage properties (tensile or shear) at different stages including initiating stage, propagation stage and failure stage, which could present the microscopic damage development process. Finally, compared with the fractures on two specimens from compressive tests, it could confirm that the meso -scale fracturing process is associated with the micro-scale damage development process.